2022
DOI: 10.1038/s41598-022-19622-6
|View full text |Cite
|
Sign up to set email alerts
|

Secondary caries and marginal adaptation of ion-releasing versus resin composite restorations: a systematic review and meta-analysis of randomized clinical trials

Abstract: This systematic review was aimed to evaluate occurrence of secondary caries and marginal adaptation in ion-releasing materials versus resin composite. Electronic search of PubMed, Scopus, and Open Grey databases with no date or language restrictions until May 21st, 2021, was conducted. Randomized clinical trials that compared ion-releasing restorations versus resin composite were included. For quantitative analysis, a random-effects meta-analysis with risk difference as an effect measure and a 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…This demographic could potentially benefit from the use of ion‐releasing restorations. A recent systematic review 44 has pointed out that in clinical trials where no significant difference was observed between ion‐releasing restorations and traditional composites, a reduction in secondary caries was evident only 45 when the patient population indicated a higher‐risk. A longer follow‐up will be conducted to identify the impact on the occurrence of secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…This demographic could potentially benefit from the use of ion‐releasing restorations. A recent systematic review 44 has pointed out that in clinical trials where no significant difference was observed between ion‐releasing restorations and traditional composites, a reduction in secondary caries was evident only 45 when the patient population indicated a higher‐risk. A longer follow‐up will be conducted to identify the impact on the occurrence of secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…The ingredients of the new ion-releasing resin composite restorative material contain glass particles and a hydrophilic ionic resin matrix that facilitates the diffusion of fluoride, phosphate and calcium ions into the surrounding environment 3 , 22 , 25 . It was reported that complete healing occurred following retrograde resin placement with 97% success rate 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using animal models, like rodents and rabbits are suitable choice for testing biological, regenerative and mineralizing characteristics of new materials in less invasive and non-critical sized surgical procedures 24 . The ingredients of the new ion-releasing resin composite restorative material contain glass particles and a hydrophilic ionic resin matrix that facilitates the diffusion of fluoride, phosphate and calcium ions into the surrounding environment 3,22,25 . It was reported that complete healing occurred following retrograde resin placement with 97% success rate 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations